2013
DOI: 10.1590/s0103-84782013005000081
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação por Amorimia spp. em ruminantes

Abstract: RESUMO No Brasil, um dos grupos mais importantes de plantas tóxicas é o das que causam morte súbita associada ao exercício. Integram esse grupo, plantas das famílias INTRODUÇÃOUm dos mais importantes grupos de plantas tóxicas no Brasil é o das que causam morte súbita associada ao exercício, que tem como principal característica a manifestação de sinais clínicos, quando os animais são movimentados. Integram esse grupo plantas das famílias Rubiaceae, Bignoniaceae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
9
0
6
Order By: Relevance
“…O controle da intoxicação por A. septentrionalis em bovinos é difícil. A remoção manual da planta é uma boa medida de controle para pequenas áreas, porém esse procedimento não é viável em áreas onde a planta está difundida (Duarte et al 2013(Duarte et al , 2013b. Outras formas de controle que têm sido experimentalmente testadas incluem a indução de aversão alimentar condicionada, a administração de doses não tóxicas da planta para induzir resistência e a administração intra-ruminal de bactérias aeróbicas que degradam o MFA (Camboim et al 2012a, 2012b, Duarte 2013a.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…O controle da intoxicação por A. septentrionalis em bovinos é difícil. A remoção manual da planta é uma boa medida de controle para pequenas áreas, porém esse procedimento não é viável em áreas onde a planta está difundida (Duarte et al 2013(Duarte et al , 2013b. Outras formas de controle que têm sido experimentalmente testadas incluem a indução de aversão alimentar condicionada, a administração de doses não tóxicas da planta para induzir resistência e a administração intra-ruminal de bactérias aeróbicas que degradam o MFA (Camboim et al 2012a, 2012b, Duarte 2013a.…”
Section: Discussionunclassified
“…As plantas que causam morte súbita associada ao exercício estão dentre as mais importantes plantas tóxicas para ruminantes no Brasil (Tokarnia et al 2012, Duarte et al 2013b. Fazem parte desse grupo, plantas das famílias Rubiaceae, Bignoniaceae e Malpighiaceae.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…As a result, a couple of species (e.g., A. rigida and A. maritima; commonly referred either as A. rigida or A. aff. rigida) have been usually considered as responsible for bovine sudden death in different parts of the country (Tokarnia et al 1961, 1990, 1994, 1996, Tokarnia & Döbereiner 1973, 1985, Medeiros et al 2002, Silva et al 2006, Melo et al 2008, Vasconcelos et al 2008, Assis et al 2009, Garcez et al 2009, Lago et al 2009, Borboleta et al 2011, Nogueira et al 2011, Schons et al 2011, Lee et al 2012, Becker et al 2013, Duarte et al 2013, Neto et al 2013, Pessoa et al 2013, Barros & Meneguetti 2014 et al 2017). Recently, broad phytochemical studies have identified monofluoracetate as the compound responsible for Amorimia's toxicity to mammals (Lee et al 2012).…”
Section: Conservationmentioning
confidence: 99%
“…Recently, broad phytochemical studies have identified monofluoracetate as the compound responsible for Amorimia's toxicity to mammals (Lee et al 2012). In the past 60 years, some methods for controlling Amorimia outbreaks became widespread among Brazilian farmers and veterinarians, such as biological, manual, and mechanical control (Duarte et al 2013, Pessoa et al 2013. Since most species of Amorimia commonly occur associated with gallery forests and waterstreams (figure 4), I believe that deforestation, associated with the increase of removal of mature individuals by farmers, has drastically affected populations of Amorimia in the past six decades.…”
Section: Conservationmentioning
confidence: 99%